2017
DOI: 10.1108/jbim-03-2017-0067
|View full text |Cite
|
Sign up to set email alerts
|

Institutional networks for supporting the internationalisation of SMEs: the case of industrial business associations

Abstract: Purpose: This paper aims to study and explore the activities and the use of institutional network resources by industrial business associations (IBAs) to support and facilitate internationalisation processes of small and medium enterprises (SMEs). Other goals are to understand the internationalisation follow-up process and the future vision of IBAs to improve this internationalisation support. Design/methodology/approach: Based on empirical evidence and following an abductive approach, this paper presents a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 60 publications
2
51
0
1
Order By: Relevance
“…Other scattered conclusions regarding the use of support services can be found within studies dedicated to their efficiency. These relate to the support services providers themselves; Costa et al (2017) explain that most industrial business associations provide continuous support for the international operations of SMEs beyond the initial stages. Furthermore, when gathering information on internationalisation, Leonidou et al (2010) observed that companies relied more on their personal networks than on institutional networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other scattered conclusions regarding the use of support services can be found within studies dedicated to their efficiency. These relate to the support services providers themselves; Costa et al (2017) explain that most industrial business associations provide continuous support for the international operations of SMEs beyond the initial stages. Furthermore, when gathering information on internationalisation, Leonidou et al (2010) observed that companies relied more on their personal networks than on institutional networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The practical knowledge was obtained from different empirical studies that we have been performing in a specific research project. Results of these empirical studies can be found in [24][25][26]. Following a DSR approach, the aim of this project was to study and design new collaboration and information management socio-technical solutions to improve the institutional network support provided by IBAs to the internationalization of SMEs.…”
Section: Case Description and Research Methodologymentioning
confidence: 99%
“…They can enable valuecreating transactions by spreading information about business partners and regulations (Betton et al, 2018;Cai − Szeidl, 2018;Johnson et al, 2002;Leonidou − Katsikeas, 1997;Pyle, 2005Pyle, , 2006bRecanatini − Ryterman, 2001), and about breaches of property rights (Pyle, 2011;Rochlitz, 2016). They can improve knowledge-sharing (Costa et al, 2017;Kirby, 1988;Luna − Tirado, 2008;Pyle, 2006a;Qiao et al, 2014) and reduce the transaction costs of coordinating shared infrastructural projects (McNamara, 1993). They can also reduce the cost of engagement with stakeholders in relation to externalities (Dickson − Arcodia, 2010) and on developing and implementing public policies (Schneider, 2010;Stolz − Schrammel, 2014).…”
Section: Levels Of Institutionalization and The Economic Roles Of Basmentioning
confidence: 99%